Comparative Study of Vitamin C Content in Kiwi and Orange Using Iodometric Titration (Shaheed Smriti Journal, 2025)
Vitamin C (ascorbic acid) is a vital nutrient known for its significant roles in human health, including antioxidant properties, collagen synthesis, immune support, and iron absorption. This comprehensive study investigates the ascorbic acid content of two commonly consumed fruits—kiwi and orange—using iodometric titration, a reliable and cost-effective technique for determining vitamin C concentrations. The research covers extensive literature review, historical background of vitamin C discovery, chemical and biological roles of ascorbic acid, methodological approaches, analytical comparisons, and implications for public health nutrition. The findings indicate that while kiwi contains higher vitamin C per 100 grams, orange contributes more per serving due to its larger average size. This study highlights the importance of accurate nutritional assessment and informed fruit consumption for daily vitamin intake.